Risk and protection strategies of Amolops wuyiensis intestine against gastrointestinal nematode (Cosmocercoides wuyiensis n. sp.) infection. (29th December 2021) - Shu, Yilin; Xie, Yunyun; Li, Shikun; Cai, Liming; Liu, Ying; Feng, Yalin; He, Jun; Zhang, Huijuan; Ran, Menglong; Jia, Qina; Wu, Hailong; Lu, Linming
Summary: Anuran amphibians are susceptible to infection by intestinal nematodes, but the damage and response mechanisms that occur in their intestines after infection are only partially understood. In this study, the intestinal disruption and response mechanisms in Amolops wuyiensis frogs infected with Cosmocercoides wuyiensis n. sp. were revealed through analysis of the intestinal histopathology, digestive enzyme activity, transcriptome and intestinal microbiota. Tissue section analysis showed histological damage and inflammation in the infected intestine, and the digestive enzyme activity indicated a decrease in digestion and absorption of some nutrients. We found that infection led to differences in the intestinal microbiota composition, including lower diversity and symbiotic relationships. The greater relative abundance of the genera Burkholderia and Rhodococcus may enhance intestinal immunity to resist pathogenic infections. A comparison of the transcriptomes of infected and uninfected intestines revealed 1055 differentially expressed genes. GO enrichment and KEGG pathways analyses suggested that the guts of infected C . wuyiensis n. sp. show enhanced complement activation, cell adhesion molecule function, NOD‐like receptor signalling pathway activity and other innate immunity responses. Among the adaptive immune responses, the intestinal immune network for IgA production was significantly enriched, and the expression of IL‐17D and transforming growth factor beta‐1 genes were upregulated in the infected intestine. These results imply that C . wuyiens is n. sp. infection of A . wuyiensis intestine may trigger innate and adaptive immune responses,  which reduce the post‐infection burden. Furthermore,  the intestine of A . wuyiensis may also respond to C . wuyiensis n. sp. infection by increasing metallocarboxypeptidase activity and accelerating smooth muscle contraction.